Temporal variations in root-associated fungal communities of Potaninia mongolica, an endangered relict shrub species in the semi-arid desert of Northwest China - Wang, Yonglong; Xu, Ying; Maitra, Pulak; Babalola, Busayo Joshua; Zhao, Yanling (Frontiers in Plant Science, 2022)
The semi-arid region of the Western Ordos plateau in Inner Mongolia, China, is home to a critically endangered shrub species, Potaninia mongolica, which originates from ancient Mediterranean regions. Root-associated microbiomes play important roles in plant nutrition, productivity, and resistance to environmental stress particularly in the harsh desert environment; however, the succession of root-associated fungi during the growth stages of P. mongolica is still unclear. This study aimed to examine root-associated fungal communities of this relict plant species across three seasons (spring, summer and autumn) using root sampling and Illumina Miseq sequencing of internal transcribed spacer 2 (ITS 2) region to target fungi. The analysis detected 698 fungal OTUs in association with P. mongolica roots, and the fungal richness increased significantly from spring to summer and autumn. Eurotiales, Hypocreales, Chaetothyriales, Pleosporales, Helotiales, Agaricales and Xylariales were the dominant fungal orders. Fungal community composition was significantly different between the three seasons, and the fungal taxa at various levels showed biased distribution and preferences. Stochastic processes predominantly drove community assembly of fungi in spring while deterministic processes acted more in the later seasons. The findings revealed the temporal dynamics of root-associated fungal communities of P. mongolica, which may enhance our understanding of biodiversity and changes along with seasonal alteration in the desert, and predict the response of fungal community to future global changes.